Modelling Vegetation Cover and Wetland Expansion in the Lower Thames Valley, UK: Multi-Proxy Records from Littlebrook Power Station, Kent. (3rd July 2021) - Stastney, Phil; Scaife, Rob; Giorgi, John; Whittaker, John E.
ABSTRACT: The interaction of 'natural' environmental processes and human activity in shaping landscapes is vividly illustrated in the Lower Thames Valley, UK. Through development-led (geo)archaeological investigations, intensifying redevelopment of this (currently) industrial landscape presents opportunities to gain long-term perspectives on these processes and to investigate the timing and extent of human impact on the environment in the past. This paper describes a novel multi-method approach undertaken at the former Littlebrook Power Station, Kent, comprising landscape-scale deposit modelling, multi-proxy palaeo-environmental analysis and vegetation cover reconstruction using REVEALS to produce schematic landscape reconstruction maps. Micropaleontological data reveal variable estuarine/freshwater influence, which alongside longer-term trends towards rising relative sea level drove lateral expansion of wetlands through the Holocene. Pollen-derived vegetation models show Early Holocene dense forest cover reduced to ∼55 per cent by 7–8 kyr BP followed by a step-change to grassland dominance in the early Bronze Age. Since grassland expansion was not proportionate to modelled expansion of wetlands but was associated with increased pastoral indicators, an anthropogenic cause of the deforestation in the Bronze Age is probable. This paper highlights the value of combining geoarchaeological data with novel modelling approaches to visualise ancient landscapes and thereby offer long-term perspectives on landscape-scale human-environment interactions.